Exploring the Resources Governance Connectivity of Cultural Ecosystem Services: Evidence in Tanjung Lesung SEZ Tourism, Banten Province, Indonesia - Kusuma, Okky Rizal; Adrianto , Luky; Kurniawan, Fery; Zulfikar , Andi (Faculty of Fisheries and Marine Universitas Airlangga, 2024)
Abstract The existence of the utilization of the Tanjung Lesung Special Economic Zone (SEZ) as connectivity, interaction relationships, and the balance of resource governance influence cultural ecosystem service. This research aimed to map out the social-ecological system components of coastal and marine cultural ecosystem services. The focus is on examining the connectivity network between resource governance (RG) components such as resource actors (RA), resource units (RU), and resource systems (RS). The data obtained were analyzed using the stages of social-ecological network analysis. The results show a significant influence and strong interaction between resource governance (RG) components and other components. The presence of institutional structures and typologies is a crucial component that serves as a guideline for SEZ management influenced by actor centrality through links. Several performance indicators are still lacking based on the interaction conditions, indicating the need for strategies to strengthen governance. However, a particular challenge that needs attention is the implementation of every governance strategy formulation. Cohesion among stakeholders in enhancing resource governance performance with the surrounding community is paramount. Improvement can be achieved through strong collaboration to ensure the sustainability of coastal and marine cultural ecosystem services. Highlight Research The components of the social-ecological system of cultural coastal and marine ecosystem services can be identified and analyzed in a case study of a special economic zone. The complexity of the social-ecological system was analyzed using a network perspective approach. Centrality analysis was used to determine the magnitude of influence of each component in the system. The performance condition of governance can be determined using analysis of the resource governance interactions.